Sequential intravesical Bacillus Calmette-Güerin and mitomycin C applied with electromotive drug administration therapy for non-muscle invasive bladder cancer - Bakula, Mirko; Hudolin, Tvrtko; Kulis, Tomislav; Zekulic, Toni; Andelic, Jerko; Zimak, Zoran; Cikic, Bojan; Juric, Ilija; Kastelan, Zeljko (Frontiers in Oncology, 2025)
Intravesical therapy plays a crucial role in reducing the risk of recurrence and progression in patients with non-muscle invasive bladder cancer (NMIBC). Among the most widely used intravesical treatments is Bacillus Calmette-Guérin (BCG). To enhance therapeutic outcomes, sequential treatment strategies have been explored, including the combination of BCG with Mitomycin C (MMC) delivered via Electromotive Drug Administration (EMDA). In this retrospective clinical study, we report the results of sequential intravesical administration of BCG and MMC administered via EMDA (MMC EMDA) in 25 patients with intermediate- and high-risk NMIBC. Primary tumors were observed in 11 patients, while 14 had recurrent disease. Only one patient experienced recurrence during follow-up, after the 3 months of the therapy, resulting in an overall recurrence rate of 4%. The median follow-up duration was 16 months. In conclusion, our results support and expand the evidence indicating that sequential BCG and MMC EMDA offer a highly effective treatment approach for patients with intermediate- and high-risk NMIBC.